Recovering Shared Objects Without Stable Storage (Extended Version) - Michael, Ellis; Ports, Dan R. K.; Sharma, Naveen Kr.; Szekeres, Adriana (University of Washington, 2017)
This paper considers the problem of building fault-tolerant shared objects when processes can crash and recover but lose their persistent state on recovery. This Diskless Crash-Recovery (DCR) model matches the way many long-lived systems are built. We show that it presents new challenges, as operations that are recorded at a quorum may not persist after some of the processes in that quorum crash and then recover. To address this problem, we introduce the notion of crash-consistent quorums, where no recoveries happen during the quorum responses. We show that relying on crash-consistent quorums enables a recovery procedure that can recover all operations that successfully finished. Crash-consistent quorums can be easily identified using a mechanism we term the crash vector, which tracks the causal relationship between crashes, recoveries, and other operations. We apply crash-consistent quorums and crash vectors to build two storage primitives. We give a new algorithm for multi-reader multi-writer atomic registers in the DCR model that guarantees safety under all conditions and termination under a natural condition. It improves on the best prior protocol for this problem by requiring fewer rounds, fewer nodes to participate in the quorum, and a less restrictive liveness condition. We also present a more efficient single-reader, single-writer atomic set—a virtual stable storage abstraction. It can be used to lift any existing algorithm from the traditional Crash-Recovery with Stable Storage model to the DCR model. We examine a specific application, state machine replication, and show that existing diskless protocols can violate their correctness guarantees, while ours offers a general and correct solution.